PEMBENTUKAN KARAKTER PESERTA DIDIK DALAM PROJEK PENGUATAN PROFIL PELAJAR PANCASILA - Rosyida Azizah; Herman Wicaksono (Program Studi Pendidikan Agama Islam UNU Purwokerto, 2024)
The Pancasila Student Profile Strengthening Project (P5) is an effort to improve the character of students including strategies, methods, design, management, assessment processing and reporting of results, evaluation and follow-up. This research uses descriptive qualitative method. Data collection techniques were observation, interview, and documentation. Data were analyzed using Miles and Huberman analysis techniques including data reduction, data presentation, and conclusion/verification. The results showed that 1) P5 design consists of forming a team, identifying school readiness, determining the dimensions of the Pancasila Student Profile character that want to be strengthened, determining the theme, planning time, flow, assessment, and creating modules; 2) P5 management includes provocation and contextualization, P5 action, and celebration of learning outcomes; 3) assessment processing and reporting of P5 results includes collecting, processing assessment results, and preparing project report cards; 4) evaluation and follow-up of P5 in the form of strengthening character and continuing good habits. Through the P5 action, it can strengthen the character dimensions of the Pancasila Student Profile in students, especially faith, devotion to God Almighty and noble character, mutual cooperation, independence, global diversity, critical and creative reasoning.